Hematobiochemical Alterations and Therapeutic Management of Meloxicam Toxicity in Deoni Bull - Chavhan, Sambhaji; Jadhav, Ravindra (International Journal of Livestock Research, 2024)
A three-year-old Deoni bull was admitted to the clinics with a history of prior treatment at a native place for mild fever and inappetence. After treatment at the native place, the affected animal started to show clinical signs such as marked anorexia and loose blackish feces with straining. Careful interrogation of the animal owner revealed prior treatment at a native place with parenteral antihistaminics, vitamin B complex, fluid therapy, oxytetracycline, meloxicam (75 mg) plus additional administration of four boluses (400 mg) of meloxicam orally in a single day. Clinical examination of the affected bull revealed normal body temperature, heart rate, respiration rate, pink pale conjunctivae, and frequent passing of loose blackish feces with straining and voiding of straw-coloured urine. Hematobiochemical analysis of the affected bull revealed a decrease in the concentration of hemoglobin and hematocrit along with a marked increase in blood urea nitrogen, creatinine, total protein, calcium, and phosphorus levels. A blood smear examination was found negative for haemoprotozoan infections. Based on the confirmed history of overdosing of meloxicam orally and parenterally along with characteristic clinical signs and hematobiochemical changes such as melena, voiding of straw-coloured urine, and marked elevation of renal biochemical parameters, the case was diagnosed for meloxicam toxicity. The affected bull was treated with fluid therapy, vitamin B complex, antihistaminics, antacids, and haematinics. Gradual clinical recovery was observed in the ailing bull with improvement in feed and water intake as well as restoration of fecal consistency and colour by the 10th day of treatment (Fig. 2). Laboratory evaluations on the 10th and 30th day revealed gradual restoration of hematological and biochemical parameters within normal reference ranges. In conclusion, accidental meloxicam overdoses in cattle can also lead to toxicity similar to one observed in pet animals characterized by loose black-coloured feces, straining while defecating, voiding of straw-coloured urine and elevated values of BUN and creatinine. Fluid therapy, supportive medications, and monitoring of kidney function and erythrogram may prove helpful in managing meloxicam toxicity in cattle.